INFLUENCE PERCEPTIONS OF LEADERSHIP STYLES WITH EMPLOYEE PRODUCTIVITY A Case Study of Cooperative Boarding School "Dasa Honor" Proponsi Yogyakarta - Utomo, Suyadi; Lastari, SE.,MM, Siwi; Nawarcono, SE., MM, Winanto (Management, 2010)
Perception research with the title of Leadership Style Effect With Employee Productivity was conducted in October 2008 until December of 2008 with respondents Employees Cooperative Boarding School "Dasa Honor" Proponsi Special Region of Yogyakarta. This study aims to determine whether leadership style affect the productivity of Cooperative Employees´ Boarding School "Dasa Honor" Proponsi Special Region of Yogyakarta. Data collection methods used were interviews and questionnaires. While the methods of data analysis used in this research is descriptive analysis method and quantitative measurement method which can be expressed with numbers. Based on the analysis of multiple linear regression equation with t test results can be seen that there is leadership style has strong relationships and significant effect on the employees of Cooperative Work Productivity Boarding School "Dasa Honor" with a t value greater than t 4.871 2.011 table so that the hypothesis proved with a value of 0.624 which means that the perception of leadership style affects employee productivity Cooperative Work on Boarding School "Dasa Honor". Keywords: Leadership, employee productivity